2021
DOI: 10.3390/ijms222212402
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Translation of Combined MAPK and Autophagy Inhibition in RAS Mutant Cancer

Abstract: RAS (rat sarcoma virus) mutant cancers remain difficult to treat despite the advances in targeted therapy and immunotherapy. Targeted therapies against the components of mitogen-activated protein kinase (MAPK) pathways, including RAS, RAF, MEK, and ERK, have demonstrated activity in BRAF mutant and, in limited cases, RAS mutant cancer. RAS mutant cancers have been found to activate adaptive resistance mechanisms such as autophagy during MAPK inhibition. Here, we review the recent clinically relevant advances i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 79 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…ERK is one of the classical signal transduction components of the MAPK family, and it can directly induce autophagy by upregulation of the expression of autophagy-related proteins such as LC3 and p62 (99). Rekha et al found that treatment with low doses of glucocorticoids increased oxidative stress levels and basal autophagy levels in osteocytes without increasing osteocyte apoptosis, whereas high doses of glucocorticoids enhanced osteocyte apoptosis.…”
Section: Ros/mapk/erkmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK is one of the classical signal transduction components of the MAPK family, and it can directly induce autophagy by upregulation of the expression of autophagy-related proteins such as LC3 and p62 (99). Rekha et al found that treatment with low doses of glucocorticoids increased oxidative stress levels and basal autophagy levels in osteocytes without increasing osteocyte apoptosis, whereas high doses of glucocorticoids enhanced osteocyte apoptosis.…”
Section: Ros/mapk/erkmentioning
confidence: 99%
“…ERK is one of the classical signal transduction components of the MAPK family, and it can directly induce autophagy by upregulation of the expression of autophagy-related proteins such as LC3 and p62 ( 99 ). Rekha et al.…”
Section: Regulation Of Autophagy In Oxidative Stressmentioning
confidence: 99%
“…As matrix metalloproteinases (MMPs) were correlated with tumor invasion via MAPK, MMPs were reduced upon the treatment with EGCG to revoke the activation of ERK and JNK, which prevented fibrosis, invasion, and migration of cancer cells ( Kim et al, 2004 ; Zhen et al, 2006 ; Ho et al, 2007 ; Zeng and Harris, 2014 ). Autophagy acts as an adaptive resistance mechanism upon the inhibition of MAPK ( Lee et al, 2021 ). MAPK signaling pathway did not solely regulate autophagy ( Raufi et al, 2021 ).…”
Section: Regulation Of Autophagy By Egcg and Green Tea Catechins In R...mentioning
confidence: 99%
“…Our results showed that the knockdown of RPIA in shRPIA#1 and shRPIA#2 A549 cells significantly diminished the cell proliferation ability, compared to the control cells (Figure 3c). [41][42][43]. Our previous studies indicated that the knockdown of RPIA can reduce cell proliferation and colony formation ability in liver cancer cells by modulating ERK signaling [15].…”
Section: Knockdown Of Rpia Decreases Colony Formation Ability and Cel...mentioning
confidence: 99%